A Comparative Study of Ground-Based and Drone-Based GPR: Opportunities, Challenges, and Applications in Bromo, Indonesia - Jannah Afni Nur; Paramita Eksi Galih Kenya; Zukhrufah Syabibah Zakiyya; Rochman Juan Pandu Gya Nur; Azhali Firmansyah Maulana (BIO Web of Conferences)
A drone-based GPR offers improved mobility and accessibility for subsurface exploration while delivering high-resolution detection of objects and soil layers, particularly in challenging areas. This study compares the performance and limitations of ground-based and drone-based GPR by analyzing their responses to surface condition using GPR radargrams. Data were collected from the Bromo-Tengger Caldera, East Java, Indonesia, using a 150 MHz antenna for drone-based GPR and a 500 MHz antenna for ground-based GPR. Data processing included filters like static correction, bandpass, gain, background removal, FK-filter, and time-to-depth conversion, with additional steps like time cut and trace editing for drone-based GPR. The results of ground-based GPR data appeared more random, with less distinct reflectors due to surface conditions like vegetation and rough terrain, despite noise filtering. Drone-based GPR faced challenges such as greater static correction due to higher altitude, and deviations from planned paths caused by GPS errors. The study concludes that both methods have unique strengths and weaknesses, and the choice between them should be based on the survey area’s conditions and project goals.